Influência da Mineração no Incremento e na Disponibilidade Geoquímica de Cobre em Sedimentos Fluviais - O Caso das Minas do Camaquã, RS, Brasil. - LAYBAUER, LUCIANO (Pesquisas em Geociências, 1996)
This work presents an analysis of copper contamination levels and copper availability in stream sediments of the João Dias Creek in the Minas do Camaquã region, caused by mineral exploitation. Fluvial sediments are predominantly sandy with less than 1% fine fraction (< 63µm), which leads to negligible amounts of environment available metals. The mean copper content in the CH3COONH4 (1M) exchangeable fraction of stream sediments showed an average availability around 7% in the region affected by mining operations. In background area this ratio is less than 2% and up to 13% in the sample point situaded downstream the sludge dam. The mean copper content in the HNO3 (0,1N) extractable fraction of stream sediments showed an average availability around 55% in the region affected by mining operations. In background area this availability is around 10% and reached 90% in the sludge dam. The pollution levels stablished by USEPA for sediments, the contamination factor (CF) and the geoaccumulation index (Igeo) determined in the fine fraction indicated a high copper contamination in the drainage segments affected by mining effluents.